Mini Review: Electrochemical Sensor for Detection of Bisphenol A (BPA) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2014)
Bisphenol A is one of the highest produced chemical in the world, which have been used broadly in many industries and commercial applications. It widely used in production of polycarbonate and epoxy resins. Worldwide production of BPA is growing rapidly and expected to reach 5.4 million tonnes by 2015. However, past research has proven BPA exhibit potential hazards to both human and environment that become a major concern in many countries. In this mini review, we have focused on recent studies on electrochemical sensors to detect BPA. Various type of electrochemical sensor has been successfully developed with good sensitivity and response.